Protocol for a single group, mixed methods study investigating the efficacy of photovoice to improve self-efficacy related to balance and falls for spinal cord injury - Hardeep Singh; Sarah Munce; Anita Kaiser; Kristin E Musselman; Katherine Chan; James D Sessford; Mohammad Alavinia (BMJ Open)
Introduction Many individuals living with spinal cord injury (SCI) experience falls and a fear of falling, both of which can impact participation in daily activities and quality of life. A single group, convergent mixed methods study will be conducted to examine the effects of a photovoice intervention on falls self-efficacy among individuals living with chronic SCI. Secondary objectives include examining the effects of photovoice on fear of falling, participation and quality of life and exploring participants’ experiences and perceptions of the photovoice intervention through qualitative interviews.Methods and analysis Adults with SCI (n=40) will be divided into groups according to their mobility status (ie, those who ambulate and those who primarily use a wheelchair). The study will be conducted virtually over three consecutive phases, totalling 30 weeks. Each group will self-report falls for 12 weeks prior to and following the intervention (phases 1 and 3, respectively). The 6-week photovoice intervention (phase 2) will be comprised of two photo assignments, two individual interviews with a researcher and a peer mentor, and four group meetings. Participants will discuss these photos at the interviews and group meetings. Standardised questionnaires of falls self-efficacy, fear of falling, participation and life satisfaction will be administered at four time points (ie, beginning of each phase and the end of phase 3). Questionnaire scores will be examined over time using repeated-measures analysis of variance. A semistructured interview will be completed at the end of phase 3 to gain feedback on the photovoice intervention. Qualitative data will be analysed using reflexive thematic analysis.Ethics and dissemination Ethics approval was obtained prior to study enrolment. Findings will be shared through peer-reviewed scientific publications and participant-directed knowledge translation activities.Trial registration number NCT04864262.